Homona spargotis Meyrick, 1910: First report on a Eucalyptus grandis W. Hill × Eucalyptus pellita F. Muell. (Myrtaceae) hybrid in Sumatra, Indonesia (Lepidoptera: Tortricidae) - T. Melia; N. G. H. B. Simulingga; M. V. Maretha; A. Nasution; A. L. Gaol; K. D. Puspita; S. K. Kkadan; W. de S. Tavares; M. Tarigan; A. Duran (SHILAP, 2022)
All potential pests (e.g., defoliating lepidopterans) of Eucalyptus L’Hér. (Myrtaceae) are important to be recorded because of multiple species from this plant genus are ubiquitously planted in forest plantations across the tropics, including Sumatra, Indonesia. The objective of this study was to record, for the first time, a species closest to the avocado leafroller, Homona spargotis Meyrick, 1910 (Lepidoptera: Tortricidae) on a Eucalyptus grandis W. Hill × Eucalyptus pellita F. Muell. hybrid in Sumatra with the insect species identification performed via molecular analysis. The used molecular protocol was able to identify a similar, yet distinct insect species to H. spargotis through analysis of its larvae, which defines its geographical distribution to Sumatra and identified a host species (i.e., E. grandis × E. pellita) for this insect.